2021
DOI: 10.3390/ijms22168808
|View full text |Cite
|
Sign up to set email alerts
|

Betulin Sulfonamides as Carbonic Anhydrase Inhibitors and Anticancer Agents in Breast Cancer Cells

Abstract: Hypoxia-regulated protein carbonic anhydrase IX (CA IX) is up-regulated in different tumor entities and correlated with poor prognosis in breast cancer patients. Due to the radio- and chemotherapy resistance of solid hypoxic tumors, derivatives of betulinic acid (BA), a natural compound with anticancer properties, seem to be promising to benefit these cancer patients. We synthesized new betulin sulfonamides and determined their cytotoxicity in different breast cancer cell lines. Additionally, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 76 publications
(118 reference statements)
0
14
0
Order By: Relevance
“…Betulin and betulinic acid are obtained through the oxidation of pentacyclic triterpene, which has been shown to have antiproliferative, anti-inflammatory, and antineovascular activity. It has an effect on various types of cancer, in vitro and in vivo [ 32 ]. Betulin, betulinic acid, lupenone, and other pentacyclic triterpenes have been found to be cytotoxic in vitro against the human adenocarcinoma and melanoma models [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Betulin and betulinic acid are obtained through the oxidation of pentacyclic triterpene, which has been shown to have antiproliferative, anti-inflammatory, and antineovascular activity. It has an effect on various types of cancer, in vitro and in vivo [ 32 ]. Betulin, betulinic acid, lupenone, and other pentacyclic triterpenes have been found to be cytotoxic in vitro against the human adenocarcinoma and melanoma models [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, adding an indole group at the C-3 position of betulin allows to obtain derivatives with enhanced anticancer activity against estrogen-receptor-positive breast tumor cells. Previously, breast cancer cells have been shown to be sensitive to certain betulin derivatives, that contain a 1,2,3-triazole ring [ 41 ] or sulfonamide group [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be concluded that the presence of the indole group at the C-28 position of the betulin skeleton increases the anticancer potential against the breast cancer cells. Similarly, Güttler et al [47] synthesized betulin sulfonamides and demonstrated their high antiproliferative and proapoptotic effects in breast cancer cells, suggesting that the betulin derivatives are promising compounds to treat aggressive breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that betulin is easily isolated from plant material and the molecule can be modified to obtain more soluble derivatives [44]. In recent years, betulin has been used as a precursor for compounds with promising anticancer properties in vitro [17,[45][46][47]. Taking this into account, as well as the fact that the indole nucleus is a biologically accepted pharmacophore in many drugs, including anticancer agents, in this study, we synthesized new 28-indole-betulin derivatives.…”
Section: Discussionmentioning
confidence: 99%